2012
DOI: 10.2147/ijn.s35576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymer size, liposomal composition, surface charge, and temperature on the permeability of pH-sensitive liposomes containing lipid-anchored poly(2-ethylacrylic acid)

Abstract: Background: Liposomes containing pH-sensitive polymers are promising candidates for the treatment of tumors and localized infection. This study aimed to identify parameters influencing the extent of contents release from poly(ethylacrylic acid) (PEAA) vesicles, focusing on the effects of polymer size, lipid composition, vesicle surface charge, and temperature. Methods: Anchored lipid pH-sensitive PEAA was synthesized using PEAA with a molecular weight of 8.4 kDa. PEAA vesicles were prepared by insertion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In vivo studies showed that conditions present within the large intestine (> pH 7.0) promoted the degradation of the Eudragit S100 films, thus triggering the collapse of the microspheres and release of over 85% of the encapsulated agents (5‐ASAs that are coated with chitosan), compared with <10% release from simulated stomach and small intestine conditions (pH 6.3). In good agreement with previous studies, the release profile in liposomes containing pH‐sensitive poly(ethylacrylic acid) (PEAA) was evaluated and found to be pH and PEAA polymer MW dependent . Maximum calcein release (80%) was achieved at pH 4.5 when the PEAA polymer mass was larger than 8.4 kDa.…”
Section: Ph‐responsive Liposomessupporting
confidence: 85%
See 1 more Smart Citation
“…In vivo studies showed that conditions present within the large intestine (> pH 7.0) promoted the degradation of the Eudragit S100 films, thus triggering the collapse of the microspheres and release of over 85% of the encapsulated agents (5‐ASAs that are coated with chitosan), compared with <10% release from simulated stomach and small intestine conditions (pH 6.3). In good agreement with previous studies, the release profile in liposomes containing pH‐sensitive poly(ethylacrylic acid) (PEAA) was evaluated and found to be pH and PEAA polymer MW dependent . Maximum calcein release (80%) was achieved at pH 4.5 when the PEAA polymer mass was larger than 8.4 kDa.…”
Section: Ph‐responsive Liposomessupporting
confidence: 85%
“…In good agreement with previous studies, the release profile in liposomes containing pH-sensitive poly(ethylacrylic acid) (PEAA) was evaluated and found to be pH and PEAA polymer MW dependent. 40 Maximum calcein release (80%) was achieved at pH 4.5 when the PEAA polymer mass was larger than 8.4 kDa. Lower PEAA polymer masses (1.2, 1.9, and 6.5 kDa) showed lower release profiles (8,35, and 70%) due to insufficient protonation of the carboxylic groups of PEAA that would trigger the conformational collapse.…”
Section: Poly(acrylic Acid)mentioning
confidence: 93%
“…Based on this result, we hypothesized that coformulation with lipids could favor self-assembly and stability at low concentrations, with the lipids acting as a "lipid skeleton" that supports the stealth peptide. Concerning the lipid part, our choice of lipid composition was based on the known thermal and mechanical stability of 4:1 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC)/cholesterol (Chol) 27 mixtures that can provide stable vesicles. Our optimization of vesicle composition started from the measurement of temperature stability and surface charge of vesicles with different percentages of L1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The effect of charge on lipid behavior is governed by the surface charge density of the liposomes, lipid head groups, and interactions between the encapsulated content and lipid [63,64]. Liposomes composed of charged polar lipids with higher electrical charges are more stable than those composed of neutral polar lipids.…”
Section: Characteristics Of Liposomesmentioning
confidence: 99%